Effect of microstructural features on the corrosion behavior of severely deformed Al–Mg–Si alloy. Issue 5 (20th November 2020) - Orłowska, Marta; Ura‐Bińczyk, Ewa; Olejnik, Lech; Lewandowska, Małgorzata
Abstract: The aim of this study was to determine the influence of severe plastic deformation processing and the changes in microstructure resulting therefrom on the corrosion resistance of an Al–Mg–Si alloy. The alloy was processed using incremental equal channel angular pressing, which caused a reduction in grain size from 15 to 0.9 µm. The grain refinement was accompanied by an increase in the number of grain boundaries and dislocations, and by changes in grain orientation. However, there was no change in the size and number of intermetallic particles, which presumably resulted in a constant number of galvanic couplings. Electrochemical experiments revealed only slight differences between the samples before and after processing. Higher potential transients/oscillations upon immersion and increased corrosion currents in the vicinity of corrosion potential point to slightly higher reactivity of the most refined material. This indicates that intermetallic particles are the most crucial microstructural elements in terms of corrosion resistance. Their impact exceeds that of grain boundaries, in particular, at the stage of corrosion initiation. The development of corrosion attack is controlled more by the microstructure of the matrix as the grain refinement resulted in a less pronounced corrosion attack in comparison with the coarse‐grained sample. Abstract : The present study investigates the influence of I‐ECAP (incremental equal channel angular pressing) processing on the corrosion resistance of an Al–Mg–Si alloy. Obtained results have shown that the influence of particles exceeds that of grain boundaries, in particular, at the stage of corrosion initiation. However, the development of corrosion attack is controlled more by the matrix.